Hybrid AC/DC electrical power grids in active buildings: a power electronics perspective - Monteiro, Vítor Duarte Fernandes (2022)
As demonstrated in the last decades, electrical power grids are in continuous pro-gress and, nowadays, more than ever, they must be prepared to deal with the grow-ing penetration of new technologies without neglecting policies targeting to mitigate climate change. Consequently, electrical grids are facing a revolution, from a cen-tralized generation paradigm (characterized by a unidirectional power flow) to a decentralized and dynamic generation (characterized by a bidirectional power flow and communication). Aligned with this context, around the world, several countries are modernizing the distribution electrical grids to obtain access to affordable, reli-able and sustainable energy.